Analysis Of The Effectiveness Of Total Neoadjuvant Therapy In The Treatment Of Patients With Rectal Cancer (Texas Journal of Medical Science, 2025)
One of the major limitations of the traditional treatment sequence is that a substantial proportion of patients are unable to complete planned adjuvant chemotherapy. Postoperative complications, prolonged recovery, stoma-related issues, and decreased performance status frequently lead to dose reductions, treatment delays, or complete omission of systemic therapy.